Functional safety for embedded systems - Xie, Guoqi, 1983- (CRC Press, 2023)
"This book uses automotive embedded systems as an example to introduce functional safety assurance and safety-aware cost optimization. The book explores functional safety assurance from the perspectives of verification, enhancement, and validation. The functional safety assurance methods implement a safe and efficient assurance system that integrates safety verification, enhancement, and validation. The assurance methods offered in this book could provide a reasonable and scientific theoretical basis for the subsequent formulation of automotive functional safety standards. The safety-aware cost optimization methods divide cost types according to the essential differences of various costs in system design and establish reasonable models based on different costs. The cost optimization methods provided in this book could give appropriate cost optimization solutions for the cost-sensitive automotive industry, thereby achieving effective cost management and control. Functional safety assurance methods and safety-aware cost optimization support each other and jointly build the architecture of functional safety design methodologies for automotive embedded systems. The work aspires to provide a relevant reference for students, researchers, engineers, and professionals working in this area or those interested in hardware cost optimization and development cost optimization design methods based on ensuring functional safety in general"--